Women’s Careers at the Start of the 21st Century: Patterns and Paradoxes - O’Neil, Deborah A. (Journal of business ethics, 2008)
In this article we assess the extant literature on women’s careers appearing in selected career, management and psychology journals from 1990 to the present to determine what is currently known about the state of women’s careers at the dawn of the 21st century. Based on this review, we identify four patterns that cumulatively contribute to the current state of the literature on women’s careers: women’s careers are embedded in women’s larger-life contexts, families and careers are central to women’s lives, women’s career paths reflect a wide range and variety of patterns, and human and social capital are critical factors for women’s careers. We also identify paradoxes that highlight the disconnection between organizational practice and scholarly research associated with each of the identified patterns. Our overall conclusion is that male-defined constructions of work and career success continue to dominate organizational research and practice., We provide direction for a research agenda on women’s careers that addresses the development of integrative career theories relevant for women’s contemporary lives in hopes of providing fresh avenues for conceptualizing career success for women. Propositions are identified for more strongly connecting career scholarship to organizational practice in support of women’s continued career advancement.